Mapping protection effects and gaps of forest dynamics in Europe 2012 to 2018 - Manuel Wolff; Benjamin Labohm; Dagmar Haase; Erik Andersson (Ecological Indicators)
Forest management and conservation can help forests adapt to and minimize the effects of natural and anthropogenic disturbance factors on forest mortality. However, little quantitative information is currently available on the impact of different management and conservation practices on forest dynamics in Europe focusing on forest extent and health simultaneously. Against this background, this paper aims to understand the effectiveness of management and protection practices on two key indicators of forest dynamics under different land use conditions. We analyzed changes in both indicators in Europe between 2012 and 2018, detected spatial explicit mean differences between forest dynamics of protected vis á vis unprotected areas, and examined protected areas of multiple management types.The results show that European forest area increased by 1.2 percentage points pp while canopy density decreased by 2 pp. The average forest area in protected areas increased, but at a slower rate than in their unprotected surroundings indicating no protection effects., In contrast, potential protection gaps can be observed for canopy density changes as density dropped in protected areas by 0.5 pp while it remained stable in unprotected areas. Finally, significant differences between IUCN management and protection categories are quantified against three settlement types and discussed along characteristic examples. In doing so, this paper contributes to the EU Forest Strategy 2030 by providing a robust and spatially explicit monitoring of the effectiveness of managed and protected forests linking observed overall patterns of forest dynamics to conclusions on the role of different management and protection practices.